Utilization of The Generate and Test Algorithm In Shortest Route Search Case - S Silvilestari (IJISTECH (International Journal of Information System and Technology), 2022)
The Gerenete and test algorithm is a very simple method in a heuristic search. The principle of this method is a combination of the depthbforst search method with backtracking because it produces a complete solution before the test process is carried out. If the work process is carried out systematically and follows the procedure, it will find a solution. The problem in this research is that if the problem is broad and large, it will likely take time to find a solution. The main purpose of this research is to test the distance in order to find a solution so as to produce a solution that is fast and saves time. Generate and test work system, namely 1. Generate a possible solution 2. Test each node which is a solution by comparing the node with the end node of a selected path with a set of expected goals. 3. If a solution has been found, then exit the system. If you haven't found a solution, then return to step 1. The final result of the research is the point F(A-B-E-I-L-T) with a heuristic number of 14